Métodos de inoculação e localização de Fusarium oxysporum f. sp. phaseoli em sementes de feijão - Lima, Poliana Patrícia (2015)
The fusarium wilt, caused by Fusarium oxysporum f. sp. phaseoli (Fop) is one of the main factors contributing to the reduction of common bean yield and the pathogen can be disseminated and transmitted by infected and / or contaminated seeds. Obtaining naturally infected seeds is one of the difficulties in practice to develop studies with the referred to pathogen in bean seeds, making it necessary to use artificial inoculation, which may be accomplished by different methods. The objective in this study was to compare methods of artificial inoculation and to verify the presence of Fop inoculum in different parts of the seed (seed coat, cotyledon and embryo axis). The study was conducted using seeds of BRS Style and isolate Fop 07, from the Mycological Collection of UFLA, and inoculation performed by three different methods: 1-soaking the seeds in water suspension with three inoculum concentrations and for five time periods, 2 - contact of seeds with the pathogen on solid agar medium without water restriction for five periods and 3- contact of seeds with the pathogen on solid agar medium with water restriction for six periods of time. From the results, it was observed that the method involving water restriction in the agar substrate produced seeds with different and higher inoculum potentials without affecting significantly the initial quality of the seeds. By this method it was shown that Fop may colonize the embryo of the seeds, causing the death of these in pre-emergence phase.